The effect of 4-way target passing training on increasing Gangga FC's passing accuracy in 2024 - galih sigaran (Sinar Lima, 2024)
Focus of the Research Problem Based on this, the author is interested in skills, there are still deficiencies in passing accuracy, therefore passing accuracy training is really needed for passing accuracy, they still use conventional and monotonous passing training models, players easily get bored in the training process.